A Study on Financial Management Constructs in Order to Improve Their Innovation Capability and Capacity: Exploring the Impact of Financial Management Constructs on Innovation Capability and Capacity in Austrian SMEs (Journal of Advances and Scholarly Researches in Allied Education, 2016)
In today's dynamic environment, creativity has become a critical component for companies seeking to expand. In this respect, financial accounting plays a critical position in enhancing a company's ability to innovate. The effect of financial management components on the innovativeness of Austrian SMEs is examined in this paper. The study found a substantial effect of the financial management paradigm on firm creativity, based on data from 118 workers from 41 SMEs in Austria. At the 1 stage, the three components of liquidity, regulation, and financial awareness are statistically important in explaining innovativeness. In order to enhance their innovation capabilities and capacity, the report recommends focusing on the three financial management constructs.